2006
DOI: 10.1139/l06-011
|View full text |Cite
|
Sign up to set email alerts
|

Integration of stochastic deterioration models with multicriteria decision theory for optimizing maintenance of bridge decks

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Liu and Frangopol presented a general computational multiobjective procedure to prioritize, annually, maintenance efforts for deteriorating reinforced concrete bridge crossheads over a designated time horizon based on condition, safety, and cost criteria (13). Morcous and Lounis proposed a formulation that integrates multicriteria decision making for maintenance optimization and stochastic Markov chains for modeling deterioration (14). This formu-lation is adopted in this study to apply Pareto trade-off analysis to bridge maintenance management.…”
Section: Formulation Of Bridge Maintenance Optimizationmentioning
confidence: 99%
“…Liu and Frangopol presented a general computational multiobjective procedure to prioritize, annually, maintenance efforts for deteriorating reinforced concrete bridge crossheads over a designated time horizon based on condition, safety, and cost criteria (13). Morcous and Lounis proposed a formulation that integrates multicriteria decision making for maintenance optimization and stochastic Markov chains for modeling deterioration (14). This formu-lation is adopted in this study to apply Pareto trade-off analysis to bridge maintenance management.…”
Section: Formulation Of Bridge Maintenance Optimizationmentioning
confidence: 99%
“…The state-based models predict bridge condition ratings using transition probabilities obtained from the difference between the two condition states at a given discrete interval. Markov chain models are one of the most common examples of the state-based models [4]. Several approaches have been developed in the past to estimate the transition probabilities of bridge components, such as the expected-value method [2], Poisson regression [5], and ordered profit model [6].…”
Section: Introductionmentioning
confidence: 99%
“…The results of a field study based on the bridge inventory database maintained by Ministere des Transports du Quebec, Canada showed that a slight improvement in the prediction accuracy from the proposed decision tree models could be achieved. Morcous and Lounis [12] also proposed a new approach which combines a Markov-chain deterioration model with two important criteria-minimization of maintenance cost and maximization of the network condition, to optimize the maintenance management of concrete bridge decks.…”
Section: Introductionmentioning
confidence: 99%